Pulmonary arterial hypertension screening of systemic sclerosis patients in clinical practice: an independent chart review. Issue 3 (September 2017) - Kelly, Dylan; Beattie, Karen A.; Larché, Maggie J.
Patients with systemic sclerosis (SSc) are at increased risk of pulmonary arterial hypertension (PAH). Guidelines recommend annual screening with pulmonary function testing (PFT) and transthoracic echocardiogram (TTE). Through auditing the charts of 11 rheumatologists associated with McMaster University, we evaluated the proportion of SSc patients without PAH or pulmonary fibrosis who receive annual TTE, PFT, and dyspnea screening. Screening rates between self-identified SSc experts and non-experts were compared. In cases where screening tests were abnormal, charts were reviewed for evidence of cardiologist or respirologist referral. In total, 136 patients' charts were included. Annual screening for dyspnea was very common (88% of patients, 119/134). Annual PAH screening via TTE (74%, 100/135) and PFT (79%, 107/136) was less common. Annual dyspnea screening, TTE, and PFT were more commonly performed by SSc experts than by non-experts (94% vs. 83%, p = 0.03; 85% vs. 61%, p = 0.002; 93% vs. 62%, p<0.001, respectively). Nearly all patients with an abnormal TTE (10/11, 91%) and PFT (12/14, 86%) received appropriate referrals. Future research should explore reasons for differences in screening rates between SSc experts and non-experts. Given that rheumatologists screen for dyspnea more often than they order PFT and TTE, there may be barriers to ordering these tests that warrant further investigation.